Implementation of knowledge management in small and medium enterprises (SMEs), Kuching - Ho, Elisa Sock Phing (2012)
This study aims to explore in the subject of implementation of Knowledge Management in Small and Medium Enterprises (SMEs) in Kuching, Sarawak. The objectives of this study are to identify level of awareness of Knowledge Management and factors affecting the implementation of Knowledge Management in SMEs. Conceptual framework was developed based on literatures. Empirical evaluation was designed with refer to conceptual framework.